1*1+2*2+3*3+4*4+5*5+6*6+7*7+8*8+9*9+n*n=1^2+2^2+3^2………………+n^21^2+2^2+3^2+4^2+5^2………………+n^2=n(n+1)(2n+1)/6利用立方差公式n^3-(n-1)^3=1*[n^2+(n-1)^2+n(n-1)]=n^2+(n-1)^2+n^2-n=2*n^2+(n-1)^2-n2^3-1^3=2*2^2+1^2-23^3-2^3=2*3^2+2^2-34^3-3^3=2*4^2+3^2-4n^3-(n-1)^3=2*n^2+(n-1)^2-n各等式全相加n^3-1^3=2*(2^2+3^2++n^2)+[1^2+2^2++(n-1)^2]-(2+3+4++n)n^3-1=2*(1^2+2^2+3^2++n^2)-2+[1^2+2^2++(n-1)^2+n^2]-n^2-(2+3+4++n)n^3-1=3*(1^2+2^2+3^2++n^2)-2-n^2-(1+2+3++n)+1n^3-1=3(1^2+2^2++n^2)-1-n^2-n(n+1)/23(1^2+2^2++n^2)=n^3+n^2+n(n+1)/2=(n/2)(2n^2+2n+n+1)=(n/2)(n+1)(2n+1)1^2+2^2+3^2++n^2=n(n+1)(2n+1)/6
(1+1+1)!=6
2+2+2=6
3x3-3=6
√4+√4+√4=6
5÷5+5=6
6+6-6=6
7-7÷7=6
8-√√(8+8)=6
√9x√9-√9=6
1 1 1=6 无解
2 +2+ 2=6
3 *3- 3=6
4 4 4=6 无解
5+ 5/ 5=6
7 -7/ 7=6
8 8 8=6 无解
9 9 9=6 无解